2018
DOI: 10.1161/strokeaha.118.021319
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Functional Connectivity Magnetic Resonance Imaging and Outcome After Acute Stroke

Abstract: Background and Purpose— Physiological effects of stroke are best assessed over entire brain networks rather than just focally at the site of structural damage. Resting-state functional magnetic resonance imaging can map functional-anatomic networks by analyzing spontaneously correlated low-frequency activity fluctuations across the brain, but its potential usefulness in predicting functional outcome after acute stroke remains unknown. We assessed the ability of resting-state functional magnetic resonance imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 52 publications
2
55
1
2
Order By: Relevance
“…In contrast to PSD, functional connectivity (FC) analysis is another approach to measure the resting-state intrinsic neuronal activity in the time domain using rsfMRI. Changes in FC value in the interhemispheric motor cortex (M1) after stroke are reportedly reflective of long-term recovery, and patients with good functional outcomes have greater FC values than patients with poor outcomes [7][8][9]. However, a recent study reported that differences in FC value in the interhemispheric M1 did not change over time with recovery [10].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to PSD, functional connectivity (FC) analysis is another approach to measure the resting-state intrinsic neuronal activity in the time domain using rsfMRI. Changes in FC value in the interhemispheric motor cortex (M1) after stroke are reportedly reflective of long-term recovery, and patients with good functional outcomes have greater FC values than patients with poor outcomes [7][8][9]. However, a recent study reported that differences in FC value in the interhemispheric M1 did not change over time with recovery [10].…”
Section: Introductionmentioning
confidence: 99%
“…One limitation of this study is that we had only the patient's structural T1 scans. It may be more informative to have access to stroke individual's diffusion or functional MRI, which have been shown to be important for extracting biomarkers that can predict impairment and recovery after stroke (Stinear et al, 2007;Siegel et al, 2016;Puig et al, 2018). One recent study showed increased baseline functional connectivity in certain regions in stroke patients who recovered better than those that did not (Puig et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It may be more informative to have access to stroke individual's diffusion or functional MRI, which have been shown to be important for extracting biomarkers that can predict impairment and recovery after stroke (Stinear et al, 2007;Siegel et al, 2016;Puig et al, 2018). One recent study showed increased baseline functional connectivity in certain regions in stroke patients who recovered better than those that did not (Puig et al, 2018). Other studies have shown biomarkers of structural white matter integrity, particularly in the motor tracts, are predictive of recovery (Stinear et al, 2007;Lindenberg et al, 2012;Rüber et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic (time-varying) functional connectivity has been explored across the lifespan (Nomi et al, 2017), across different states of consciousness (Deco et al, 2017b;Escrichs et al, 2019;Lord et al, 2019), in patients with brain disorders (Puig et al, 2018), and during healthy aging (Tian et al, 2018;Nobukawa et al, 2019). One study that evaluated resting-state fMRI data from 250 subjects to examine patterns of resting-state functional connectivity over time found that dynamic connectivity patterns are consistent across groups (Abrol et al, 2016).…”
Section: Introductionmentioning
confidence: 99%